Mengoptimalkan Produktivitas Kerja di PT SEN Melalui Analisis Kebutuhan Karyawan Menggunakan Metode Quality Function Deployment - Hard, Evin; Harahap, Uun Novalia; Utama, Denny Walady (CV. IRA PUBLISHING, 2023)
This research highlights the importance of meeting employee needs to increase work efficiency and effectiveness at PT SEN, a company operating in the oil and gas industry. Using the Quality Function Deployment (QFD) method, this research aims to translate employee desires into technical attributes that management can implement. Through surveys and data collection from 25 respondents, the service attributes desired by employees have been identified, evaluated for validity and reliability, and linked to company performance. The research results show that several attributes, such as laptops with high specifications, comfortable workspaces, and integrated work dashboards, are top priorities for PT SEN employees. Service attribute performance is evaluated through the House of Quality (HOQ) matrix, and target values are set, guiding the improvement and development of necessary facilities and infrastructure. The analysis also leads to identifying unnecessary or less essential attributes of employees. In conclusion, QFD is a practical approach to determining priorities for meeting the needs of PT SEN employees. The analysis results provide significant insight to direct management in improving the work environment and service for employees by focusing on the attributes most prioritized by employee teams.